The effect of Elaeagnus angustifolia flower essence inhalation on dyspareunia and sexual satisfaction of women at reproductive age: A randomized clinical trial - Behnaz Jafari; Raheleh Babazadeh; Roshanak Salari; Jamshid Jamali; Tahereh Sadeghi (Mashhad University of Medical Sciences, 2021)
Introduction: Sexual satisfaction is a key factor in quality of life that depends on several factors including healthy, pleasant and painless sexual relations. Treatment of sexual dysfunction should be given special attention due to the impact on the relationship between couples and family stability. This study was performed with aim to determine the effect of inhalation of Elaeagnus angustifolia flower essence on dyspareunia and sexual satisfaction of women at reproductive age. Methods: This three-group randomized clinical trial study was performed on 99 women referring to health centers in Mashhad in 2019-2020. The study's units were assigned into three groups. The first group used the essence for 4 weeks, 3 times a day for 20 minutes each time and the second group once only 20 minutes before intercourse as inhalation and the third group did not receive any intervention. The Sexual Function Index (FSFI) was completed before the intervention and at the end of the 4th week after the intervention in all three groups. Data were analyzed by SPSS software (version 21) and one-way analysis of variance, Chi-square and Kruskal-Wallis tests. P<0.05 was considered statistically significant. Results: The mean score of sexual pain after the intervention in the first intervention group was 4.3±0.8, in the second intervention group was 4.7±0.7 and in the control group was 4.0±0.8. Based on the results of the intra-group test, the intervention was significantly increased only in the second intervention group (p<0.05). The mean score of sexual satisfaction after the intervention in the first intervention group was 4.2±0.7, in the second intervention group was 4.7±0.9 and in the control group was 3.8±0.5. Based on the results of intra-group test, the intervention was significantly increased only in the second intervention group (p<0.001). Conclusion: Inhalation of Elaeagnus angustifolia essence 20 minutes before intercourse can effectively increase sexual satisfaction by reducing pain and discomfort during sexual intercourse. Therefore, it can be used as an affordable herbal supplement with minimal side effects.